Resolving complex structural variants via nanopore sequencing - Romagnoli, Simone; Bartalucci, Niccolò; Vannucchi, Alessandro Maria (Frontiers in Genetics, 2023)
The recent development of high-throughput sequencing platforms provided impressive insights in the human genetics field and contributed to consider structural variants (SVs) as the hallmark of the genome instability leading to the establishment of several pathologic conditions including neoplasia, neurodegenerative and cognitive disorders. While SVs detection was addressed by Next Generation Sequencing (NGS) technologies, more recent the introduction of long read sequencing technologies have already been proven invaluable to overcome the inaccuracy and limitations of NGS technologies when applied to resolve wide and structurally complex SVs due to the short length (100-500 bp) of the sequencing read employed. Among the long read sequencing technologies, Oxford Nanopore Technologies developed a sequencing platform based on protein nanopore that allows the sequencing of “native” long DNA molecules of virtually unlimited length (typical range 1-100Kb). In this review we focus on the bioinfomatics methods that improves the identification and the genotyping of known and novel SVs to investigate human pathological conditions discussing the possibility of introducing nanopore sequencing technology into routine diagnostics.